Study of yield and its components for twenty genotypes of Triticale under different planting dates - Mohammed, Balssam Mansour; Mohammed, Mohammed Ibrahim (Journal of Kerbala for Agricultural Sciences, 2022)
In this study, 20 genotypes of triticale (RWAIDA, AMAL, MOHAND, FRAH, POLLMER, LIRON, HUI/TUB, HUI/TUB-1, CENT/1715, BW32-1-1, CMH80, CMH82, POPP-CAAL, CAAL, LIRON -1, LIRON -2, LIRON -3, LIRON -4, LIRON -5, and LIRON -6) were used the experiment was planted according to the design of randomized complete block design by the split-plot arrangement the plant dates putting in main plot (5 November, 20 November, and 5 December), and genotypes in subplot the results show: the first date exceeded the grain yield per plant, number of spikes per plant, number of grains per spike, weight 1000 (g), as it reached 17.16 gm plant-1, 5.91spike, 86.33 grain, and 40.22 gm respectively. The LIRON-2 genotype was superior in the number of spikelets per spike with a mean of 40.15 and number of grain per spike with a mean of 97.28 and yield of grain with a mean of 18.71 gm plant-1 and the genotype of LIRON-3 in some spikes with a mean of 5.64 and biological yield of 47.65 gm plant-1.